The impact of Transformational Leadership on Innovative Work Behavior, the Mediating Role of Employee Engagement and Psychological Capital in Karachi Hospitals - Sagar Singh; Essa Khan; Asif Rehman (International Journal of Business and Economic Affairs, 2023)
This study investigates how TL processes affect IWB in healthcare systems, particularly hospitals, and how PsyCap and EE function as mediators. Based on the responses of 187 various hospital managers in Karachi, it was found that TL influences IWB indirectly via PsyCap and EE. We employed a quantitative research strategy for this study. Cross-sectional sampling, convenience sampling, and SEM-PLS analysis make up the methodology. The total number of participants was 187 in which 67 (35.8%) were females and 120 (64.2%) were males. If the p Values are less than 0.05 and/or the t statistic value is more significant than 1.96, the hypothesis can be accepted (Hair & Alamer, 2022). The results of the path coefficient test showing that EE has a positive significant impact on IWB as the p value is (0.027 < 0.05). PsyCap has a positive significant impact on IWB as the p value is (0.016 < 0.05). TL has a positive significant impact on EE as the p-value is (0.000 < 0.05). TL has a positive significant impact on IWB as the p-value is (0.001 < 0.05). TL has a positive significant impact on PsyCap as the p-value is (0.000<0.05). The sample size of this study was small, and the results may not be generalizable, future studies may increase the sample size to improve the reliability of the results. This study only used hospitals in Karachi; future research may broaden its scope to include other areas. Furthermore, the current study employed a cross-sectional design. Future researchers should use a longitudinal design that collects data at multiple time points to increase the credibility of the findings. Future studies should include additional mediating variables such as Thrive at Work, Customer Engagement, and Mind Effect to deepen our understanding of the various leadership styles and their effects on healthcare.